Report of the third external programme and management review of the International Food Policy Research Institute (IFPRI) - Review Panel (Consultative Group on International Agricultural Research, 1998)
The Panel made four recommendations covering IFPRI's research work, stressing water and globalization, outreeach activities, impact assessment, and the relevance of IFPRI's activities. The Panel also encouraged IFPRI's Board to take a more active role in ensuring and monitoring the relevance and impact of the center's work.